Analisis Komparatif Kinerja Emas dan Bitcoin sebagai Alternatif Instrumen Investasi - Andri Wahyu Pratama; Eka Yuliyanti (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
Global economic uncertainty has raised concerns among the public, triggering actions to secure economic stability by investing, especially in gold and bitcoin. This study uses a comparative quantitative method, with the aim of comparing the returns, risks, and performance of the two investment instruments. The population in this study is in the form of data on the monthly closing prices of gold and bitcoin for the period of January 2019 – April 2025 which totals 152 data, consisting of 76 data from each variable. Data analysis was carried out by calculating returns, risks, Sharpe, Treynor and Jensen indices. The three indices are widely used performance measurement methods and have included return and risk factors in their measurements. The results of this study show that there is a significant difference between the return of gold and bitcoin, while for the risk variable between the two, there is no significant difference. Performance based on the Sharpe method also showed no significant difference between the two. However, for performance measurement using the Treynor and Jensen methods, significant differences were obtained between the two instruments. Overall, bitcoin offers higher profit potential than gold, even more so for investors who can accept high volatility. However, the decision to choose an investment instrument still depends on the risk profile of each investor.